Microwave-assisted preparation of yeast cells for ultrastructural analysis by electron microscopy - Moritz Mayer; Christina Schug; Stefan Geimer; Till Klecker; Benedikt Westermann (Microbial Cell)
Budding yeast Saccharomyces cerevisiae is widely used as a model organism to study the biogenesis and architecture of organellar membranes, which can be visualized by transmission electron microscopy (TEM). Preparation of yeast cells for TEM can be quite challenging and time-consuming. Here, we describe an optimized protocol for conventional fixation of yeast cells with potassium permanganate combined with cell wall permeabilization with sodium metaperiodate and embedding in Epon. We have replaced time-consuming incubation steps by short treatments with microwaves and developed a microwave-assisted permanganate fixation and Epon embedding protocol that reduces the time required for sample preparation to one working day. We expect that these protocols will be useful for routine analysis of membrane ultrastructure in yeast.